THU0168 Relationships between body fat composition assessed with bioelectrical impedance analysis, serum adipokines and disease activity in patients with rheumatoid arthritis. (12th June 2018) - Anelli, M.G.; Venerito, V.; Lopalco, G.; Cacciapaglia, F.; Scioscia, C.; Giannotta, M.; Righetti, G.; Montini, F.; Natuzzi, D.; Bizzoca, R.; Lacarpia, N.; Fanizzi, R.; et al.
Abstract : Background: High-grade inflammation in patients affected with Rheumatoid Arthritis (RA) leads to an imbalanced body composition characterised by increased fat mass and decreased lean mass, with stable or increased body weight, resulting in little or no change in body mass index (BMI). 1 This condition, known as rheumatoid cachexia, is proven to be reversible once inflammatory process has been shut down. BMI and waist-to-hip ratio (WHR) are used as indirect measurements of visceral fat even if not capable of discriminating it from subcutaneous fat tissue. An alternative method proposed for assessment of fat composition, indicating nutritional status, is bioelectrical impedance analysis (BIA). Objectives: To analyse body fat composition of patients with RA assessed using either BIA and anthropometric measures, investigating relationships between the related indices, serum adipokines and disease activity. Methods: The body composition of 87 consecutive patients (72 female, 82.76%) affected with RA according to 2010 ACR/EULAR classification criteria, mean age of 52.42±13.29, mean disease duration of 10.71±8.58 years, treated with DMARDs and/or biologics, was assessed during their visit to our outpatient department. Data including demographic characteristics clinical manifestations, disease activity indices (DAS28-ESR, DAS28-CRP, CDAI, SDAI), Health Assessment Questionnaire (HAQ), lipid profile, as well as radiological findings were collected. Patients underwent to anthropometric measures (WHR and BMI) and BIA for the evaluation of fat-free mass (FFM), fat mass (FM) and the derived indices (fat-free mass index (FFMI) and fat mass index (FMI)). In addition for each patient blood samples were collected to determine serum levels of several adipokines (leptin, adiponectin, visfatin, resistin). Statistical tests as well as linear and logistic regression analysis were carried out. Results: DAS28-ESR was found to be related to FMI (p=0.02; r = 0.22) and to BMI (p=0.03; r=0.22). In addition, in patients in whom DAS28-ESR remission was not achieved, FMI but not BMI was found to be related to the latter disease activity index (p=0.007, r=0.37). FMI was shown to correlate to HAQ (p=0.01, r=0.31). Higher serum levels of leptin were found to predict higher FMI and BMI (p<0.0001 for both, r=0.68 and r=0.57, respectively) with DAS28 being also related to the latter adipokine (p=0.02; r=0.24). FFMI was inversely related to adiponectine serum levels (p=0.0003; r=- 0.40). Both male and female patients classified as underweight for BMI were found to have a normal mean FFMI, with both groups presenting a mean DAS28-ESR score indicating remission. Conclusions: Either body fat composition assessed with BIA-related indices and serum leptin have been noticed to predict disease activity. Moreover nutritional status of patients in remission according to DAS28-ESR may be better assessed by determining indices brought by BIA along with BMI, in order to rule out rheumatoid cachexia on the basis of FMI and FFMI. Reference: [1] Ferraz-Amaro I, Gonzalez-Juanatey C, Lopez-Mejias R, Riancho-Zarrabeitia L, Gonzalez Gay MA. Metabolic syndrome in rheumatoid arthritis. Mediators Inflamm2013. Disclosure of Interest: None declared